What are the Effects and Results of Fuse Periodicals on the Transformation of Digital Fonts? - Sarikavak, Anıl (ARTic, 2025)
Unlike Emigre, the international typography periodical Fuse has a different mission. In addition to having a conceptual publishing policy with a separate concept in each publication, the experimental fonts prepared by designated experts for these concepts actually expanded the boundaries of the font design concept of the period and fulfilled a pioneering and creative task in the context of the inspirations or sources of design. It is possible to see the effects of Fuse not only in the 1990s or 2000s, but also throughout the 2010s. In the literature in our country, the effects and contributions of the Fuse periodical to the development of graphic design have not been examined much, and the qualities of the fonts developed thanks to the magazine are not well understood. The purpose of this article, which will be based on literature review as a qualitative research method, is to define the mission fulfilled by Fuse and to contribute to the literature on the qualities of the fonts developed by the publication. Keywords: Digital Publishing, Digital Typography, Fuse, Digital Font, Expertimental Font